A Study on the Development of Key Performance Indicators (KPIs) At an Aerospace Manufacturing Company - Mohamad, Effendi; Muhamad, Mohd Razali; Abdullah, Rohana; Adi , Saptari (Penerbit UTeM, 2008)
This research study focuses on the issue of the Key Performance Indicators (KPIs) development which is linked to the goal, objective, mission and vision of an Aerospace Manufacturing Company. The KPIs are targeted to provide this company with a good performance measurement tools in supporting the success of their Lean Manufacturing journey and to be cost-competitive. In this study, a set of KPIs measured both objectively and subjectively are developed through a comprehensive extensive literature, internal benchmark activities and best practices benchmark in KPIs implementation process flow. Additionally, the current communication gap at all level was investigated by using semi-structure interview and focus group discussion. A standard report is created to overcome this communications issue by having each person in each level to review and reports their standard operation to their subordinates regularly based on agreed frequency.